Fabian Holt, Genre in Popular Music (2007) - Marx, Wolfgang (Journal of the Society for Musicology in Ireland, 2008)
A review of Fabian Holt, Genre in Popular Music (Chicago and London: University of Chicago Press, 2007), ISBN 978-0-226-35039-4, xiv + 221 pp, £10.00/€16.99 (paperback)